Enhanced photocatalytic hydrogen production from Y2O3/TiO2 nano-composites: a comparative study on hydrothermal synthesis with and without an ionic liquid. (25th February 2016) - Ravishankar, T. N.; de Oliveira Vaz, M.; Khan, S.; Ramakrishnappa, T.; Teixeira, S. R.; Balakrishna, Geetha R.; Nagaraju, G.; Dupont, J.
Abstract : The synthesis of Y2 O3 /TiO2 nano-composites via hydrothermal and ionic liquid assisted hydrothermal methods, for photocatalytic hydrogen production. Abstract : Hetero-junction Y2 O3 /TiO2 nano-composite (NC) photocatalysts were synthesized using a conventional hydrothermal method (Y2 O3 /TiO2 NC(HM) ) and an ionic liquid assisted hydrothermal method (Y2 O3 /TiO2 NC(ILAHM) ). The composite nature and physico-chemical properties of the photocatalysts prepared through both routes as a function of thermal treatment were investigated via thorough characterization. A comparison of the photocatalytic hydrogen production via water splitting is provided. It was found that the concentration of Y2 O3 in the TiO2 matrix and the post thermal treatment have obvious effects on the hydrogen production activity, and they were fine-tuned for enhancement of the hydrogen production. The required synergy between Y2 O3 and TiO2 was found to occur at an optimum concentration of 25 wt% Y2 O3 in the TiO2 matrix, with the sample prepared at 400 °C for 1 h. The optimized NC i.e. 25 wt% Y2 O3 /TiO2 NC(ILAHM) produced a promising hydrogen evolution of 1380 μmol g −1 that was almost 2-fold the production from 25 wt% Y2 O3 /TiO2 NC(HM) . The enhancement was attributed to the porous surface morphology, higher surface area and quantum yield of the NC prepared using the ionic liquid assisted hydrothermal method.